Seawater carbonate chemistry and oyster physiological performance - Caillon, Coline; Fleury, Elodie; Di Poi, Carole; Gazeau, Frédéric; Pernet, Fabrice (PANGAEA, 2025)
This study investigated the physiological responses of juvenile Pacific oyster Crassostrea gigas exposed for 81 days to current and ocean acidification and warming conditions (+3 ◦C, − 0.3 pH units) under two tidal treatments (0 vs. 30 % emersion) and two food levels (ad libitum vs. limited). We measured growth, reproduction, food ingestion, respiration, and biochemical traits like energy reserves and membrane fatty acids. At the experiment's end, oysters were challenged with a viral disease to assess the physiological cost of acclimation and potential trade-offs. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were downloaded from SEANOE (see Source) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-04-17.
Keywords: Animalia; Behaviour; Benthic animals; Benthos; Coast and continental shelf; Containers and aquaria (20-1000 L or < 1 m**2); Crassostrea gigas; Growth/Morphology; Immunology/Self-protection; Laboratory experiment; Mollusca; North Atlantic; Other; Other studied parameter or process; Reproduction; Respiration; Single species; Temperate; Temperature